(untitled) (Ágora UNLaR, 2019)
Este trabajo explora los roces entre la ciencia ficción y el policial en la primera novela de la serie “Quint” del escritor escocés Paul Johnston, Body Politic (1997). Expresamos que una de las tantas razones por las que el policial es interesante es debido a que se trata de un género que rebasa, desde sus comienzos, los límites literarios, incorporando otros géneros o esfumando los límites y dominios de algunos géneros que parecen consolidados. Creemos que éste es el caso del policial y la ciencia ficción en, al menos, este texto de Johnston, el cual, a partir de una estructura novelística más flexible que otros clásicos policiales, inserta elementos de la ciencia ficción a aquellos propios del policial negro y, en particular, de la novela de suspenso. Johnston añade un peculiar desplazamiento temporal, propio de una sátira política o distopía, al mejor estilo de Gulliver’s Travels (1726) de Swift, Brave New World (1932) de Huxley, Nineteen Eighty-four (1949) de Orwell, o Do Androids Dream of Electric Sheep? (1968) de Dick. Incorporando elementos propios de la autorreferencialidad a una trama policial que se sitúa en un futuro distópico, Body Politic reúne todas las condiciones para considerarlo un texto que disuelve los límites genéricos, para luego integrarlos en lo que podríamos denominar, de manera tentativa, un policial de ciencia ficción autorreferencial. Indagaremos en estas cuestiones, con especial atención en aquellos elementos prestados de estos géneros e integrados en una trama detectivesca sin duda peculiar. ALTERNATIVES TO SCOTTISH DETECTIVE FICTION: SCIENCE FICTION AND THE HARD-BOILED Abstract This paper explores the relation between science fiction and detective fiction in the first novel from the "Quint" series by the Scottish writer Paul Johnston, Body Politic (1997). We state that one of the many reasons why detective fiction is interesting is the fact that it is a genre that reaches far beyond, from its beginnings, the literary limits, incorporating other genres or blurring the boundaries and domains of some genres that seem to be consolidated. We believe that this the case of detective fiction and science fiction in, at least, this text by Johnston, which, from a novel structure more flexible than other classical detective novels, embeds elements from science fiction to those specific to the noir novel and, in particular, from the suspense novel. Johnston adds a peculiar time shift, typical of the political satire or the dystopian novel, in the best tradition of Gulliver’s Travels (1726) by Swift, Brave New World (1932) by Huxley, Nineteen Eighty-Four (1949) by Orwell, or Do Androids Dream of Electronic Sheep? (1968) by Dick. Incorporating elements typical of autoreferentiality to a detective storyline that is situated in a dystopian future, Body Politic satisfies the formal requirements to be considered as a text that dismantles generic limits, to integrate them later on in what we could call, in a tentative way, autoreferential detective science fiction. We will explore these matters, paying special attention to those elements borrowed from these genres and integrated in an undeniably eccentr ic detective storyline. Keys word: science fiction, hard-boiled, detective stories